Crisis management during anaesthesia: recovering from a crisis. Issue 3 (2nd June 2005) - Bacon, A K; Morris, R W; Runciman, W B; Currie, M
Abstract : Preventing harm to the patient is the priority during a crisis. After a major incident, and especially when a patient has been harmed, there are a number of matters to be addressed: the ongoing care of the patient; documentation of the incident; investigation of the root causes; completion of reports; interviews with the patient and/or the next of kin, together with apologies and expression of regret; updates and ongoing support for friends and relatives; a word of thanks to the staff involved for their assistance; formal debriefing of staff for quality assurance and possibly ongoing support and a separate debriefing for psychological purposes; ensuring that the recommendations of the root cause analysis are carried out; or, failing that, that the issues are logged on a risk register. The extent and depth of the follow up protocol depends on what, if any, harm may have been done. This may constitute completion of an incident report; notification of an equipment failure to a federal regulatory authority; arranging consultations with a mental health professional to manage psychological sequelae (especially following an awareness episode); follow up during weeks of intensive care treatment; or, when a death has occurred, a full medico-legal and/or coronial set of procedures. A précis is appended in an action card format.